2021
DOI: 10.1002/pbc.29098
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing participation rates in clinical late‐effect studies of childhood cancer survivors

Abstract: To ensure external validation of a study population in clinical late-effect studies of childhood cancer, the participation rate must be high. This study investigated demographic data in Nordic late-effect studies and potential factors impacting participation rates such as cancer type, time since diagnosis, and duration of clinical examinations.We found 80 published studies originating from 16 cohorts, with median follow-up of 6.0 years (range 3-14). The overall participation rates ranged from 27% to 100%. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…They found that overall participation rates ranged from 27% to 100% and speculated that more personalized recruitment strategies could increase participation rates. Our preliminary results confirm the finding that time since diagnosis does not influence participation [ 27 ]. Age at diagnosis also does not have a measurable impact.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…They found that overall participation rates ranged from 27% to 100% and speculated that more personalized recruitment strategies could increase participation rates. Our preliminary results confirm the finding that time since diagnosis does not influence participation [ 27 ]. Age at diagnosis also does not have a measurable impact.…”
Section: Discussionsupporting
confidence: 89%
“…The overall participation rate in the LESS-Anthra study was only 30%, and not all LESS-Anthra participants were also willing to participate in the pharmacogenetic substudy. The participation rate is at the lower end of the range of figures reported in the literature [27]. We attempted to give as many eligible patients as possible the opportunity to participate, regardless of whether or not they were followed up closely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation